9(x+8)=8(x-8)+x

Simple and best practice solution for 9(x+8)=8(x-8)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+8)=8(x-8)+x equation:


Simplifying
9(x + 8) = 8(x + -8) + x

Reorder the terms:
9(8 + x) = 8(x + -8) + x
(8 * 9 + x * 9) = 8(x + -8) + x
(72 + 9x) = 8(x + -8) + x

Reorder the terms:
72 + 9x = 8(-8 + x) + x
72 + 9x = (-8 * 8 + x * 8) + x
72 + 9x = (-64 + 8x) + x

Combine like terms: 8x + x = 9x
72 + 9x = -64 + 9x

Add '-9x' to each side of the equation.
72 + 9x + -9x = -64 + 9x + -9x

Combine like terms: 9x + -9x = 0
72 + 0 = -64 + 9x + -9x
72 = -64 + 9x + -9x

Combine like terms: 9x + -9x = 0
72 = -64 + 0
72 = -64

Solving
72 = -64

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 | | 8y-2=-6y+50 | | -10=2+2.4w | | 5.8-1.4=16 | | 9(g+2)-4=7g+3(3g+8) | | 7(st)=(7s)t | | 5w+a=4.8+8w | | -(3b-15)=6(2hb+5) | | -4m-23=5 | | 2y=-5x+12 | | 5w+9=4.8+8w | | 25+5x=-80-2x | | -4.9t^2+355t+87=0 | | 22(2y+1)= | | 2x+2(2x+8)=772 | | 20-2z=26 | | 3z-4z=2 | | 4x+9.8=5.8x-5.86 | | 2(x-5)=3(x-4) |

Equations solver categories